Optimizing The Health Of The Dental Supporting Network In Labuhan Ratu Raya Village, Labuhan Ratu District Through Village Community Guidance - Suryani Catur Suprapti; Indah Budiarti; Rizki Nurul Fatimah; Sepriana Urianti; Sri Wahyuni; Sri Murwaningsih; Aryudhi Armis (Yayasan Jompa Research and Development, 2026)
Problems with supporting tissue health, such as gingivitis, periodontitis, tartar, and loose teeth, are still quite common among the elderly in Labuhan Ratu Raya. This condition is influenced by a lack of understanding of oral hygiene, improper brushing techniques, and a lack of awareness of routine dental checkups. In response to this situation, the community service team conducted a series of educational activities, examinations, and training involving the elderly, their families, and health cadres. The health cadres also expressed their readiness to continue routine coaching for the elderly in their respective communities. Overall, these activities have had a positive impact on improving the oral health of the elderly in Labuhan Ratu Raya Village. It is hoped that these coaching activities will continue and become part of ongoing efforts to prevent periodontal problems, thereby further improving the quality of life for the elderly in the area.